DIFFERENCES IN THE EFFECTIVENESS OF DENTAL HEALTH EDUCATION USING SONGS AND POSTERS ON TOOTH BRUSHING KNOWLEDGE - Sabila Maghfuroh Aqsha Syahari; Isnur Hatta; Galuh Dwinta Sari; Diana Wibowo; Rosihan Adhani (Dentin, 2024)
Background: Based on Riskesdas (2018), the largest proportion of dental problems in Indonesia are damaged teeth/cavities/toothache, one of the reasons is the low proportion of tooth brushing behavior. Banjarbaru City is the area with the lowest prevalence in the South Kalimantan region in the right time to brush teeth with the proportion is only 2,06%. Bloom divided behavior into 3 domains, namely knowledge, attitudes, and actions. One of the efforts to increase knowledge maintaining oral health can be through Dental Health Education used songs and posters. Purpose: Analyzing the differences in the effectiveness of Dental Health Education using the Healthy Teeth song and the Read Me poster on increasing knowledge of brushing teeth of class VI students at SDN 2 Loktabat Selatan. Methods: used a quasi-experimental design method with a non-equivalent control group design. Sampling technique used was total sampling technique. The research was conducted at SDN 2 Loktabat Selatan with a sample of 79 respondents. Results: Wilcoxon showed that there were differences in knowledge of brushing teeth before and after DHE using the Healthy Teeth song and Read Me posters in the intervention group (p=0,000) and there was no difference in knowledge of brushing teeth between pretest and posttest in the control group (p=0,809). Mann Whitney showed that there were differences in knowledge of brushing teeth between the song and poster groups (p=0,001), but the mean rank of the song group was higher. Conclusion: DHE using the Healthy Teeth song was more effective in increasing knowledge of brushing teeth.